Analysis Of SIMRS Implementation Using HOT-Fit Model with SEM-PLS Approach - Amrullah Rahman Farisi; Ghea Sekar Palupi (Journal of Education Technology and Information System, 2026)
The Hospital Management Information System (SIMRS) is an information and communication technology system that manages and integrates all hospital service processes. The goal of this research is to investigate the impact of human, organizational, and technological factors on net benefits in implementing SIMRS at RSUD dr. Wahidin Sudiro Husodo. This study uses the Human Organization Technology (HOT) Fit information system analysis model consisting of system quality, information quality, service quality, compatibility, self-efficacy, system usage, user satisfaction, organizational structure, organizational environment, and net benefits. This research method uses quantitative analysis based on respondent data, namely SIMRS users at RSUD dr. Wahidin Sudiro Husodo Mojokerto City. The data was then analyzed using the SEM-PLS method and the SmartPLS 4 software. The findings revealed that only organizational structure can significantly impact net benefits directly.